Quantitation of tadalafil in human plasma using a sensitive and rapid LC-MS/MS method for a bioequivalence study - Abhaysingh Bhadoriya; Bhavesh Dasandi; Dharmesh Parmar; Priyanka A. Shah; Pranav S. Shrivastav (Elsevier, 2018)
A highly sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the determination of tadalafil (TAD) in human plasma. TAD and its deuterated internal standard (IS), tadalafil-d3, were extracted from 200 µL plasma using Phenomenex Strata-X-C 33 µ extraction cartridges. Chromatographic analysis was carried out on Synergi™ Hydro-RP C18 (100 mm × 4.6 mm, 4 µm) column with a mobile phase consisting of methanol and 10 mM ammonium formate, pH 4.0 (90:10, v/v), delivered at a flow rate of 0.9 mL/min. Quantitation of the protonated analyte was done on a triple quadrupole mass spectrometer using multiple reaction monitoring via electrospray ionization. The precursor to product ions transitions monitored for TAD and TAD-d3 were m/z 390.3 → 268.2 and m/z 393.1 → 271.2, respectively. The calibration curve was linear over the concentration range of 0.50-500 ng/mL with correlation coefficient, r2 ≥ 0.9994. Acceptable intra-batch and inter-batch precision (≤ 3.7%) and accuracy (97.8% to 104.1%) were obtained at five concentration levels. The recovery of TAD from spiked plasma was highly precise and quantitative (98.95% to 100.61%). Further, the effect of endogenous matrix components was minimal. TAD was found to be stable under different storage conditions in human plasma and also in whole blood samples. The validated method was successfully used to determine TAD plasma concentration in a bioequivalence study with 20 mg TAD tablets in 24 healthy volunteers. Method performance was evaluated by reanalyzing 115 study samples. Keywords: Tadalafil, Tadalafil-d3, LC-MS/MS, Sensitive, Bioequivalence study, Human plasma